2022
DOI: 10.1017/cjn.2022.70
|View full text |Cite
|
Sign up to set email alerts
|

prepOSCE: A Virtual, Scalable Solution to Prepare Residents for Their OSCE Examination

Abstract: The Royal College Comprehensive Objective Examination in Neurology provides certification for Canadian neurologists and consists of a written examination and the Observed Structured Clinical Encounter (OSCE). The OSCE portion of the certification involves residents visiting several patient stations where they address case scenarios with an examiner. Unfortunately, residents lack exam preparation time due to demanding work hours. In response to resident needs, we created a novel, virtual preparation OSCE progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…Many educational facilities for healthcare professionals, including residents, medical, nursing, pharmacy, and dentistry students, rapidly transitioned from traditional in-person OSCEs to virtual OSCEs (also described as remote OSCE, online OSCE, or tele-OSCE) (Felthun et al, 2021a;Malau-Aduli et al, 2022). These virtual OSCEs are satisfactory, feasible, and cost-effective as per survey results (Langenau et al, 2014;Shaban et al, 2021;Shaiba et al, 2021), questionnaire feedbacks (Skrzypek et al, 2022;Motkur et al, 2022;Garofalo et al, 2023), empirical analysis (Felthun et al, 2021b;Minty et al, 2022), and descriptive qualitative studies (Shorbagi et al, 2022;Saad et al, 2022;Thampy et al, 2022;). Although three studies assessed the reliability of virtual OSCEs by calculating Cronbach's alphas, and they were about 0.80 (Oliven et al, 2011(Oliven et al, , 2021Porto et al, 2023), a reliability analysis based on G-theory is yet to be reported (Kunutsor et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Many educational facilities for healthcare professionals, including residents, medical, nursing, pharmacy, and dentistry students, rapidly transitioned from traditional in-person OSCEs to virtual OSCEs (also described as remote OSCE, online OSCE, or tele-OSCE) (Felthun et al, 2021a;Malau-Aduli et al, 2022). These virtual OSCEs are satisfactory, feasible, and cost-effective as per survey results (Langenau et al, 2014;Shaban et al, 2021;Shaiba et al, 2021), questionnaire feedbacks (Skrzypek et al, 2022;Motkur et al, 2022;Garofalo et al, 2023), empirical analysis (Felthun et al, 2021b;Minty et al, 2022), and descriptive qualitative studies (Shorbagi et al, 2022;Saad et al, 2022;Thampy et al, 2022;). Although three studies assessed the reliability of virtual OSCEs by calculating Cronbach's alphas, and they were about 0.80 (Oliven et al, 2011(Oliven et al, , 2021Porto et al, 2023), a reliability analysis based on G-theory is yet to be reported (Kunutsor et al, 2022).…”
Section: Introductionmentioning
confidence: 99%